ANALISIS STRUKTUR VELG PADA MODIFIKASI AIRSIDE INSPECTION VEHICLE MENGGUNAKAN PERANGKAT LUNAK ANSYS - Oka Fatra; Ego Widoro; Tony Yudhyika Pradana Gultom (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
Airside Inspection Vehicle is a vehicle designed by cadets of Airport Mechanical Engineering 6 from the vehicle tossa three wheels become the four wheel. The component of vehicle has never been done tested. A strength testing of wheel material against static working load is calculated using static structural and force theory and then compared by using software R17.0 Ansys Workbench. The tested area are flange and hub diameter. The vehicle load of 500 kg, the stress that occurs at flange using theoretical is 0,382 MPa and count software is 0,0002 MPa while stress that happen at hub diameter area is 10,74 MPa and count software is 18,671 with allowable stress of 110 MPa. The Result showed that the stress occurs at the velg considered safe.